Figurative Language Analysis Found in Montgomery Ricky Album - Tazkiyatul Wildaniyah; Afiifah Al Rosyiidah (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Figurative language is the language that is often used in daily activities, in poetry, novels, and songs. The use of this language requires analysis because it cannot be interpreted literally. The purpose of this study is to examine in which figurative language is used as well as the function of figurative language in Montgomery Ricky's album. The words, phrases, or sentences in song lyrics that contain figurative language are the data of this study. These data are analyzed using Hatch & Brown's (1955) theory of figurative language types and Perrine's (1977) theory of the function of figurative language. The documentation method is used to categorize materials related to the issues discussed in data collection. The interactive qualitative approach proposed by Miles et al., (2014) is utilized in data analysis, including the following steps: (1) data condensation; (2) data display; and (3) conclusion. The study's findings indicate that figurative language is used in the Montgomery Ricky album. There are 65 figurative language data, including 18 metaphors, 16 metonymies, 11 hyperboles, 5 personifications, 4 synecdoche, 3 antitheses, 2 ironies, 2 apostrophes, 2 paradoxes, 1 allusion, and 1 understatement. Oxymoron and metaphor are two types of figurative language that are not encountered. 4 The purpose of using figurative language based on Perrine (1977) theory, that are as additional imaginary, imaginative pleasure, emotional intensity, and means of concentration found in the analysis.